Quasi-3D Thermal Modelling of Advanced Electronic Systems in Package - Petrosyants, Konstantin O.; Ryabov, Nikita I. (Theory and Applications of Engineering Research Vol. 3, 2024)
Because the semiconductor devices sizes are getting smaller and power density is growing, the complete thermal modelling is necessary to keep the balance between the electrical power and heat dissipation. The traditional method using the universal physical fully-3D simulators becomes not effective because of the complexity and particularly much CPU time for numerical solution. Therefore the thermal properties types of modern packages were not yet completely investigated. A Quasi-3D approach was introduced for simplification and speeding up the numerical thermal modelling of electronic systems in package (SiP). The main features of SiP constructions were taken into account: 1) 3D integration of ICs and the board; 2) a large number of thinned layers of different materials; 3) short vertical z-axis interconnections through the package layers. The complex 3D problem transforms in the more simple problem described by the system of 2D equations for the set of the package layers. The software tool Quasi-3D-Overheat focused for SiP thermal simulation was developed. In comparison with commercial universal physical fully-3D simulators, the pre- and post- data processing is simplified and CPU time considerably (in 5 - 10 times) is decreased while saving the sufficient accuracy. The simulation error of the maximum temperature TMAX for different types of packages is not more than 10–20%.